(untitled) (Al-Academy, 2023)
The creative production of the philosophy of beauty in artistic works constitutes a step towards development and progress by meeting the growing and changing needs of humanity according to various factors, including those related to the human situation and others related to technical outputs, as well as the multiplicity of the field for the emergence of new artistic currents and movements concerned with graphic production and communication and communication processes that It is associated with imagination and freedom from social and cultural constraints, in which the design production seeks to link more realistic intellectual contents with the achievements of the creative artwork as a communication system to involve the recipient (the viewer) in achieving paths of development in the aesthetic taste. Rather, research, excavation, and exploration of beauty and its artistic goals in order for the recipient to move from the role of the viewer or listener to the role of the participant as a reader and critic with his philosophy, experience, and culture that are determined by his social and cultural conditions and intellectual orientations, especially for those posts through social networking sites that strip thought through openness and freedom from all restrictions. Accordingly, the viewer recipient has a role in expressing opinion, admiration, analysis and characterization according to skills that have been acquired gradually, conditional and unconditional. Most institutions seek to achieve their readings in all dimensions, including the aesthetic dimension, to reach the highest level of achieving aesthetic reception and absorption of the productions in all their graphic, photodigital, fixed and mobile classifications.